(untitled) (ModaPalavra e-periódico, 2016)
Within the women’s clothing of the universe’s underwear were long an insignificant plan with regard to the development of new textile materials, shapes and colors. The panties that had been known as breeches or long underwear only became a necessity around the twentieth century with the vaporous dresses Christian Dior in the 50 Technological advances in the textile industry brought spandex created by the American laboratory DuPont’s better known as the lycra. The elasticity of the fabric gave comfort to women’s lingerie, passing this attribute to be considered as a quality factor in lingeries. To understand the desires of the users a qualitative research was conducted with women 18-45 years collecting opinions on theperceived comfort of already existing models compared to a new one be launched. Through the Quality Function Deployment Tool (QFD), or Quality Function Deployment, the data obtained from users of the answers given an interpretation which is to prioritize targets for the development of a based product on analyzes of desired characteristics which are converted into attributes technicians.